The Teaching Practices of Social Studies Teachers and the Four Cs of 21st Century Skills of Aeta Learners in Subic District, Schools Division of Zambales, Philippines - A. Paz, Patrick Jordan (International Journal of Humanities and Education Development (IJHED), 2021)
The aim of this study was to determine the relationship of the teaching practices in the field of Social Studies and the Four Cs of the 21st Century Skills of the Aeta Learners in the District of Subic, Zambales, Philippines. The study has a descriptive correlational design. It was made use of the descriptive-survey, checklist method and rubrics. Based on findings, the Aeta students were found to have a "Good” level of Creativity, Collaboration, Critical Thinking and Communication Skills in both pre assessment and post-assessment while the social studies teacher’s Teaching Practices were found to be “sometimes” applied in the teaching and learning process. The results also show a positive moderate relationship between the teachers' Teaching Practices as to "Delivery" and the Aeta learners' Creativity, Critical Thinking and Communication Skills and a positive low relationship between the teacher-respondents' applied Delivery and the Aeta learners' Collaboration Skill. Results also show a positive moderate correlation between the Teaching Practices under "Evaluation" and the Creativity, Critical Thinking and Communication Skills of the Aeta learners. Based on the results, the researcher recommended School Administration and Teachers to adopt initiatives and establish good two-way communication, create opportunities to connect, establish a school-wide structured opportunities for parents’ involvement and communicate often about the need for and importance of parental involvement, and teachers must engage students more on learner-centered approach, expose students on experimenting, exploring, questioning, creating assumptions, using analysis, imagination, synthesizing information and evaluation.